Enhancing Vocabulary Through Simpler Digital Applications: An Epistemological Approach to Language Learning - Baihaqi, Baihaqi; Manugeren, M. Manugeren; Barus, Efendi (Journal of English Language and Education, 2025)
This study aimed to enhance of vocabulary mastery at junior high school students level through simpler digital application. Vocabulary is a fundamental aspect of English learning, yet many junior high school students struggle to acquire sufficient vocabulary, which hinders their ability to develop other language skills. To address this issue, the simpler application was introduced as a digital learning medium that provides simple, interactive, and accessible vocabulary practice. This research argues that digital applications can serve as epistemic mediators, allowing learners to build vocabulary through meaningful interaction and autonomous learning. Quantitative approach used with a pre-experimental design, specifically a one group pre-test and post-test model. The participants consisted of 23 students selected through purposive sampling. A vocabulary test was administered before and after five sessions of treatment using the Simpler application. The collected data were analyzed using descriptive and inferential statistics, including a paired sample t-test. The results showed that the students’ post-test mean score was significantly higher than the pre-test mean score. The obtained t-value (6.247) exceeded the critical value of the t-table (2.074) at the 5% significance level, confirming that the improvement was statistically significant. These findings indicate that the simpler application is enhance in improving students’ vocabulary mastery with epistemological principles of meaningful learning.